Increasing the chance of dying at home: roles, tasks and approaches of general practitioners enabling palliative care: a systematic review of qualitative literature - Shangavi Balasundram; Anne Holm; Kirstine Skov Benthien; Frans Boch Waldorff; Susanne Reventlow; Gritt Overbeck (BMC Primary Care, 2023)
Abstract Background Many elderly people wish to die at home but end up dying at the hospital. If the patient wishes to die at home, palliative care provided by General Practitioners (GPs) may increase the chance of dying at home, however, there is a lack of knowledge on how GPs should provide palliative care. We aimed to identify roles, tasks and approaches of GPs enabling palliative care, by exploring the experiences of GPs, other healthcare professionals, patients, and relatives through a systematic review of the qualitative literature. Methods We searched PubMed, EMBASE, PsycINFO, Web of Science, and CINAHL in March 2022. Thematic analysis was used for synthesizing the results. Results Four thousand five hundred sixty three unique records were retrieved, and 12 studies were included for review. Of these, ten were interview or focus group studies and two were survey studies with additional open-ended questions. Only qualitative findings from the studies were used in synthesizing the results. Thematic analysis produced four main themes describing the roles, tasks and approaches of GPs enabling palliative care to increase the chance for patients to die at home. GPs can support patients in the final phases of life by applying a holistic, patient-centred, and proactive approach to palliative care and by having sufficient education and training. Furthermore, the palliative care consultation should include symptom management, handling psychosocial and spiritual needs, maintaining a fragile balance, and proper communication with the patient. Lastly, GPs must address several palliative care elements surrounding the consultation including initiating the palliative care, being available, being the team coordinator/collaborator, providing continuous care and having sufficient knowledge about the patient. Conclusions The roles, tasks and approaches of the GPs enabling palliative care include being aware of elements in the palliative care consultation and elements surrounding the consultation and by having sufficient education and training and a broad, proactive, and patient-centred approach.